Touching! An Augmented Reality System for Unveiling Face Topography in Very Young Children - Miyazaki, Michiko; Asai, Tomohisa; Mugitani, Ryoko (Frontiers in Human Neuroscience, 2019)
Developmental body topography, particularly of the face, is a fundamental research topic in the current decade. However, empirical investigation of this topic for very young children faces a number of difficulties related to the task requirements and technical procedures. In this study, we developed a new task to study the spatially-sensed position of facial parts in a self-face recognition task for 2.5- and 3.5-year-old children. Using the technique of augmented reality (AR) and 3D face tracking technology, we presented participants with their projected self-image on a screen, accompanied by a digital mark located on parts of their face. We prepared a cheerful visual and auditory reward on the screen when participants showed correct localization of the mark. We then tested whether they could indicate the position of the mark on their own faces and remain motivated for task repetition. To assess the efficacy of this task, thirty-one 2.5- and eleven 3.5-year-old children participated in this study. About half of the 2.5-year-olds and 80% of the 3.5-year-olds could perform more than 30 trials. Our new task, then, was to maintain young children’s motivation for task repetition using the cheerful visual and auditory reward. The analysis of localization errors suggested the uniqueness of spatial knowledge of self-face in young children. The efficacy of this new task for studying the development of body image has been confirmed.